2018
DOI: 10.1088/2057-1976/aada67
|View full text |Cite
|
Sign up to set email alerts
|

Long-term stability of neural signals from microwire arrays implanted in common marmoset motor cortex and striatum

Abstract: Current neuroprosthetics rely on stable, high quality recordings from chronically implanted microelectrode arrays (MEAs) in neural tissue. While chronic electrophysiological recordings and electrode failure modes have been reported from rodent and larger non-human primate (NHP) models, chronic recordings from the marmoset model have not been previously described. The common marmoset is a New World primate that is easier to breed and handle compared to larger NHPs and has a similarly organized brain, making it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 65 publications
(80 reference statements)
3
12
0
Order By: Relevance
“…It was found that over a course of 12 weeks, there was an increase in recording failure among the MEAs. Similar phenomena were observed in a study by Debnath et al, where MEAs were implanted into marmoset brains and monitored for signal stability and quality over the course of several months. Over time, many of the MEAs lost signal stability, with only 2 of 11 MEAs showing long‐term stability.…”
Section: Biocompatibility and Performance Assessment Of Microelectrodsupporting
confidence: 82%
See 1 more Smart Citation
“…It was found that over a course of 12 weeks, there was an increase in recording failure among the MEAs. Similar phenomena were observed in a study by Debnath et al, where MEAs were implanted into marmoset brains and monitored for signal stability and quality over the course of several months. Over time, many of the MEAs lost signal stability, with only 2 of 11 MEAs showing long‐term stability.…”
Section: Biocompatibility and Performance Assessment Of Microelectrodsupporting
confidence: 82%
“…As a result, without good cell adhesion, MEAs are free to move around in the brain, causing additional strain on the surrounding tissue 41b. Not only does this cause damage to the brain, but it also compromises MEA function over time . Adding to this problem is the ensuing FBR following MEA insertion.…”
Section: Future Outlookmentioning
confidence: 99%
“…Although a complete comparison between these types of array is beyond the scope of this proof-of-concept tool introduction, we believe it is likely that the variations in performance observed with ‘Utah’ arrays in macaques were larger than for the 3D arrays we used. In fact, in marmosets, arrays with similar sizes as the ones used in this study (but with fewer electrode contacts) have been reliably implanted and often measured spiking activity for months ( Debnath et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Utilization of primates in IME studies have shown the potential clinical applications of the electrodes, but unfortunately suffer from the same decline in recording performance (Chestek et al, 2011;Barrese et al, 2013Barrese et al, , 2016. Recent work introducing a marmoset model also displayed similar signal degradation found in traditional animal models (Debnath et al, 2018). Rodent models yield similar electrode reliability results compared to the larger animal alternatives.…”
Section: Introductionmentioning
confidence: 92%